TPU (thermoplastic polyurethane) foaming material recycled from leftover materials of shoe materials and preparation process of TPU foaming material

By recycling and processing of shoe scraps and using modified mica powder, combined with melt blending of TPU particles and supercritical fluid foaming technology, the problem of degradation of wear resistance after shoe scraps is solved, and a shoe foaming material with high wear resistance and good resilience is achieved.

CN119662014APending Publication Date: 2025-03-21FENGTE (FUJIAN) NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411590274.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

During the processing of shoe materials, if the scraps of shoe materials are directly recycled and used during foaming, it will lead to a degradation of the wear resistance of the material.

Method used

The TPU foaming material for recycling shoe scraps and its preparation process is adopted. The scraps are processed by using a recycling treatment agent and an antibacterial agent, and the modified mica powder is melted and blended with raw materials such as TPU particles, and then supercritical fluid foaming is carried out in an autoclave.

Benefits of technology

It significantly improves the wear resistance of foamed materials, while maintaining the toughness and rebound properties of the materials, extending service life and reducing wear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005125393560000111
    Figure BDA0005125393560000111
  • Figure BDA0005125393560000121
    Figure BDA0005125393560000121
Patent Text Reader

Abstract

The invention relates to the field of shoe materials, and particularly discloses a TPU (thermoplastic polyurethane) foaming material recycled from leftover materials of shoe materials and a preparation process of the TPU foaming material. The TPU foaming material recycled from the shoe material leftover materials is prepared from the shoe material leftover materials, a recycling treatment agent, TPU particles, modified mica powder, a cross-linking agent, an antibacterial agent and an antioxidant. Wherein the preparation raw materials of the modified mica powder comprise ureido silane, di (triethanolamine) diisopropyl titanate and mica powder, and the mica powder is modified through the ureido silane and the di (triethanolamine) diisopropyl titanate, so that the mica powder is uniformly dispersed in a polyurethane matrix, the agglomeration phenomenon is reduced, and the wear resistance of the material is improved. And moreover, the shoe material leftover materials are recycled for secondary utilization, so that the production cost is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of shoe materials, and in particular to a TPU foaming material obtained by recycling shoe material scraps and a preparation process thereof. Background Art

[0002] Thermoplastic polyurethane (TPU) is a new synthetic material between rubber and plastic. It has been widely used in various fields of people's daily life due to its excellent comprehensive performance. Thermoplastic polyurethane has excellent rebound performance, wear resistance, processing performance, etc. It can be repeatedly processed and used. TPU material can be used as the preparation material of the sole after foaming.

[0003] In the process of shoe material processing, the shoe material foaming process can be roughly summarized as: material mixing and granulation, foaming molding, cutting of foamed materials, and making finished products. Among them, a large amount of scraps will be generated in the cutting process. If these scraps are discarded, it will cause a certain amount of waste. Therefore, recycling and reusing the scraps can reduce production costs. However, since these shoe material scraps have undergone one or more foaming processes, if the scraps are directly mixed with other raw materials to make foamed materials, the wear resistance of the material will decrease. Summary of the invention

[0004] In order to improve the wear resistance of the foam material, the present application provides a TPU foam material recycled from shoe material scraps and a preparation process thereof.

[0005] In the first aspect, the present application provides a TPU foam material recycled from shoe scraps, which adopts the following technical solution:

[0006] A TPU foam material recycled from shoe material scraps is prepared from the following raw materials in parts by weight:

[0007] 45-55 parts of leftover shoe materials, 15-19 parts of recycling agent, 80-90 parts of TPU particles, 8-12 parts of modified mica powder, 1-2 parts of cross-linking agent, 0.6-0.8 parts of antibacterial agent, 0.3-0.5 parts of antioxidant;

[0008] The raw materials for preparing the modified mica powder include urea silane, diisopropyl di(triethanolamine)titanate and mica powder, and the weight ratio of the urea silane, diisopropyl di(triethanolamine)titanate and mica powder is (0.4-0.6):(0.1-0.3):10.

[0009] By adopting the above technical scheme, the present application recycles the footwear material scraps with a recycling treatment agent and an antimicrobial agent. Since the footwear material scraps are contaminated before recycling, the colony count in the footwear material scraps can be effectively reduced by adding an antimicrobial agent. In addition, the footwear material scraps are recycled and processed again, which reduces production costs, reuses resources, and realizes the renewable and recyclable resources. Modified mica powder is added to the polyurethane resin matrix, and the mica powder can improve the wear resistance of the foaming material. Wherein, by urea silane and di (triethanolamine) diisopropyl titanate, the two act synergistically, entangled with each other, cross-linked, and composite modification is carried out on the mica powder, the compatibility between the mica powder and the polyurethane matrix is ​​increased, and the mica powder is evenly dispersed in the polyurethane matrix, reducing the occurrence of agglomeration, which is conducive to improving the wear resistance of the material.

[0010] Preferably, the ureidosilane is one or both of 3-ureidopropyltrimethoxysilane and 3-ureidopropyltriethoxysilane.

[0011] By adopting the above technical solution, the alkoxy groups in the urea silane are hydrolyzed and combined with the hydroxyl groups on the surface of the mica powder to form a coupling agent molecule layer on the surface of the mica powder. The coupling agent molecule layer can chemically crosslink or entangle with the polyurethane molecules, and finally combine the mica powder and the polyurethane molecules well and fill the gaps between the polyurethane molecules, thereby improving the wear resistance of the foaming material. In addition, the urea silane can also reduce the surface energy of the mica powder, improve the compatibility of the mica powder with the resin matrix, and make the resin matrix have better processing performance.

[0012] Preferably, the preparation method of the modified mica powder is:

[0013] First, mica powder is added to a NaOH solution, stirred at 40-50°C for 1-2 hours, filtered under reduced pressure to remove excess water and dried to obtain pretreated mica powder; then, urea silane and di(triethanolamine)titanate diisopropyl are mixed to obtain a composite modified liquid, and then the composite modified liquid is added to an ethanol solution, the pH is adjusted to 6.5-7.5, and stirred at a temperature of 50-60°C for 2-3 hours to obtain a hydrolysis solution; finally, the pretreated mica powder is added to the hydrolysis solution, stirred evenly, filtered and washed after standing for 3-4 hours, and the modified mica powder is obtained after drying.

[0014] By adopting the above technical scheme, the number of hydroxyl groups on the surface of the mica powder can be increased by pre-treating the mica powder. The mica powder is compositely modified by urea silane and di(triethanolamine)titanate diisopropyl to form an active layer on the surface of the mica powder, which is helpful for the combination of the powder and the polyurethane molecules, effectively improving the compatibility of the mica powder, and making the powders have good dispersion without obvious agglomeration.

[0015] Preferably, the recovery treatment agent is trimethylamine hydrochloride solution.

[0016] By adopting the above technical solution and using a recycling agent to pre-treat shoe material scraps and improve the performance of the foaming material, it is possible to not only increase the recycling rate of resources and reduce production costs, but also improve environmental benefits and achieve the renewable and recyclable materials.

[0017] Preferably, the cross-linking agent is one or more of dicumyl peroxide, di(tert-butylperoxyisopropyl)benzene, benzoyl peroxide, and tert-amyl peroxypivalate.

[0018] By adopting the above technical solution, the peroxide cross-linking agent is helpful to promote the cross-linking reaction, and generates free radicals to initiate the combination between polymer chains to form a three-dimensional network structure, thereby improving the strength and wear resistance of the foamed material.

[0019] Preferably, the antibacterial agent is alkyl trimethyl ammonium salt, dialkyl dimethyl ammonium salt, benzyl alkyl dimethyl ammonium salt.

[0020] By adopting the above technical solution, quaternary ammonium salts can destabilize bacterial cell membranes through transmembrane action, thereby causing membrane fusion and cell lysis. At the same time, quaternary ammonium salts can also combine with negative ions on the surface of bacteria, interfering with the enzyme system and metabolic process of the organism, hindering its normal growth and reproduction.

[0021] Preferably, the antioxidant is one or more of antioxidant 1010, antioxidant 1079, antioxidant 245, antioxidant 1076, antioxidant 3114, and antioxidant 1726.

[0022] By adopting the above technical solution, the antioxidant has the ability to remove free radicals by polymerizing with the free radicals in the reaction, so that the electron pairs on the free radicals are changed, no excess electrons are generated, and no chain reaction occurs, thereby effectively reducing the degree of oxidation of the material and slowing down the oxidation process of the material.

[0023] Preferably, the TPU particles are polyester polyurethane with a Shore hardness of 50A-45D.

[0024] By adopting the above technical solution, the polyester polyurethane with a Shore hardness of 50A-45D has better wear resistance and strength.

[0025] In the second aspect, the present application provides a preparation process of a TPU foam material recycled from shoe material scraps, which adopts the following technical solution:

[0026] A preparation process of a TPU foam material recycled from shoe material scraps, comprising the following steps:

[0027] S1: crushing the leftover shoe materials to obtain leftover material fragments, mixing the leftover material fragments with a recycling treatment agent and an antibacterial agent, stirring and reacting at 45-55° C. for 3-4 hours, and drying to obtain recycled TPU particles;

[0028] S2: melt-blending the recycled TPU particles with a cross-linking agent, TPU particles, modified mica powder, and an antioxidant at 140-150° C., and pelletizing underwater to obtain composite TPU particles;

[0029] S3: placing the composite TPU particles in a high-pressure reactor, introducing a supercritical fluid, fully impregnating at a temperature of 130-140° C. and 16-20 MPa, releasing the pressure, and steam molding to obtain a TPU foam material.

[0030] By adopting the above technical solution, the modified mica powder has an enhanced effect in TPU foaming materials, which can significantly improve the strength and wear resistance of the foaming materials, while not affecting the toughness and resilience of the materials, making them more durable during use, extending their service life and reducing the degree of wear. By recycling the leftovers of shoe materials and converting them into reusable TPU particles and making them into foaming materials, this process significantly improves the utilization rate of raw materials and reduces the impact of waste generated during the production process on the environment.

[0031] Preferably, the supercritical fluid in S3 is one or both of supercritical CO2 and supercritical N2.

[0032] By adopting the above technical solution, using the special properties of CO2 or N2 in a supercritical state, supercritical CO2 or supercritical N2 is injected into the device, mixed with other molten raw materials to form a single-phase mixed glue, and the gas is precipitated by reducing the pressure to form a large number of bubble nuclei. In the subsequent cooling process, the bubble nuclei continue to grow and form, and finally a microporous foamed shoe material is obtained. Compared with chemical foaming, the present application uses physical foaming to avoid the problem of residual byproducts caused by chemical decomposition, which is more green and environmentally friendly. In addition, the bubbles obtained by the physical foaming method are more uniform, and the performance of the obtained shoe material is better.

[0033] This application has the following beneficial effects:

[0034] In the present application, the present application recycles the footwear scraps with a recycling agent and an antimicrobial agent. Since the footwear scraps are contaminated before recycling, the colony count in the footwear scraps can be effectively reduced by adding an antimicrobial agent. In addition, the footwear scraps are recycled and processed again, which reduces production costs, reuses resources, and realizes the renewable and recyclable nature of resources. Modified mica powder is added to the polyurethane resin matrix, and mica powder can improve the wear resistance of the foaming material. Wherein, by urea silane and di (triethanolamine) diisopropyl titanate, they are mutually entangled, cross-linked, and composite modification is carried out on mica powder, the compatibility between mica powder and the polyurethane matrix is ​​increased, and mica powder is evenly dispersed in the polyurethane matrix, reducing the occurrence of agglomeration, which is conducive to improving the wear resistance of the material. DETAILED DESCRIPTION

[0035] Preparation Example

[0036] Preparation Example 1

[0037] Preparation method of modified mica powder:

[0038] First, 10 kg of mica powder (sericite powder) was added to a NaOH solution, stirred at 40 ° C for 1 hour, filtered under reduced pressure to remove excess water and dried to obtain pretreated mica powder; then, 0.4 kg of 3-ureapropyltrimethoxysilane and 0.1 kg of di(triethanolamine)titanate diisopropyl were mixed to obtain a composite modified liquid, and then the composite modified liquid was added to an ethanol solution, the pH was adjusted to 6.5, and stirred at a temperature of 50 ° C for 2 hours to obtain a hydrolysis solution; finally, the pretreated mica powder was added to the hydrolysis solution, stirred evenly, filtered and washed after standing for 3 hours, and the modified mica powder was obtained after drying.

[0039] Preparation Example 2

[0040] Preparation method of modified mica powder:

[0041] First, 10 kg of mica powder (sericite powder) was added to a NaOH solution, stirred at 45 ° C for 1.5 hours, filtered under reduced pressure to remove excess water and dried to obtain pretreated mica powder; then, 0.5 kg of 3-ureapropyltrimethoxysilane and 0.2 kg of di(triethanolamine)titanate diisopropyl were mixed to obtain a composite modified liquid, and then the composite modified liquid was added to an ethanol solution, the pH was adjusted to 7.0, and stirred at a temperature of 55 ° C for 2.5 hours to obtain a hydrolysis solution; finally, the pretreated mica powder was added to the hydrolysis solution, stirred evenly, filtered and washed after standing for 3.5 hours, and the modified mica powder was obtained after drying.

[0042] Preparation Example 3

[0043] Preparation method of modified mica powder:

[0044] First, 10 kg of mica powder (sericite powder) was added to a NaOH solution, stirred at 50 ° C for 2 hours, filtered under reduced pressure to remove excess water and dried to obtain pretreated mica powder; then, 0.6 kg of 3-ureapropyltriethoxysilane and 0.3 kg of di(triethanolamine)titanate diisopropyl were mixed to obtain a composite modified liquid, and then the composite modified liquid was added to an ethanol solution, the pH was adjusted to 7.5, and stirred at 60 ° C for 3 hours to obtain a hydrolysis solution; finally, the pretreated mica powder was added to the hydrolysis solution, stirred evenly, filtered and washed after standing for 4 hours, and the modified mica powder was obtained after drying.

[0045] Preparation Example 4

[0046] Preparation method of modified mica powder:

[0047] First, 10 kg of mica powder (sericite powder) was added to a NaOH solution, stirred at 40 ° C for 1 hour, filtered under reduced pressure to remove excess water and dried to obtain pretreated mica powder; then, 0.4 kg of 3-mercaptopropyltrimethoxysilane and 0.1 kg of di(triethanolamine)titanate diisopropyl were mixed to obtain a composite modified liquid, and then the composite modified liquid was added to an ethanol solution, the pH was adjusted to 6.5, and stirred at a temperature of 50 ° C for 2 hours to obtain a hydrolysis solution; finally, the pretreated mica powder was added to the hydrolysis solution, stirred evenly, filtered and washed after standing for 3 hours, and the modified mica powder was obtained after drying.

[0048] Example

[0049] Example 1

[0050] A TPU foam material recycled from leftover shoe materials, comprising 55kg of leftover shoe materials, 15kg of trimethylamine hydrochloride solution (with a concentration of 15wt%), 90kg of TPU particles (polyester polyurethane with a Shore hardness of 50A), 8kg of modified mica powder (prepared in Preparation Example 1), 1kg of diisopropylbenzene peroxide, 0.6kg of alkyltrimethylammonium salt, and 0.3kg of antioxidant 1010.

[0051] The preparation process of the TPU foam material recycled from the leftovers of shoe materials in this embodiment includes the following steps:

[0052] First, the leftover shoe materials are crushed to obtain leftover fragments, the leftover fragments are mixed evenly with trimethylamine hydrochloride solution and alkyl trimethylammonium salt, stirred and reacted at 45° C. for 3 hours, and then dried to obtain recycled TPU particles;

[0053] Next, the recycled TPU particles were melt-blended with dicumyl peroxide, TPU particles, modified mica powder, and antioxidant 1010 at 140° C. and pelletized underwater to obtain composite TPU particles.

[0054] Finally, the composite TPU particles are placed in a high-pressure reactor, supercritical CO2 is introduced, and the TPU foam material is obtained after full impregnation, pressure release, and water vapor molding at a temperature of 130°C and 16MPa.

[0055] Example 2

[0056] A TPU foam material recycled from leftover shoe materials, comprising 60kg of leftover shoe materials, 17kg of trimethylamine hydrochloride solution (with a concentration of 20wt%), 95kg of TPU particles (polyester polyurethane with a Shore hardness of 45D), 10kg of modified mica powder (prepared in Preparation Example 2), 1.5kg of di(tert-butylperoxide isopropyl)benzene, 0.7kg of dialkyldimethylammonium salt, and 0.4kg of antioxidant 1726.

[0057] The preparation process of the TPU foam material recycled from the leftovers of shoe materials in this embodiment includes the following steps:

[0058] First, the leftover shoe materials are crushed to obtain leftover fragments, and the leftover fragments are evenly mixed with trimethylamine hydrochloride solution and dialkyl dimethyl ammonium salt, stirred and reacted at 50° C. for 3.5 hours, and then dried to obtain recycled TPU particles;

[0059] Next, the recovered TPU particles were melt-blended with di(tert-butylperoxyisopropyl)benzene, TPU particles, modified mica powder, and antioxidant 1726 at 145° C., and pelletized underwater to obtain composite TPU particles;

[0060] Finally, the composite TPU particles were placed in a high-pressure reactor, supercritical N2 was introduced, and the TPU foaming material was obtained after full impregnation, pressure release, and water vapor molding at a temperature of 135°C and 18MPa.

[0061] Example 3

[0062] A TPU foam material recycled from leftover shoe materials, comprising 65kg of leftover shoe materials, 19kg of trimethylamine hydrochloride solution (with a concentration of 25wt%), 100kg of TPU particles (polyester polyurethane with a Shore hardness of 50A), 12kg of modified mica powder (prepared in Preparation Example 3), 2kg of benzoyl peroxide, 0.8kg of benzyl alkyl dimethyl ammonium salt, and 0.5kg of antioxidant 3114.

[0063] The preparation process of the TPU foam material recycled from the leftovers of shoe materials in this embodiment includes the following steps:

[0064] First, the leftover shoe materials are crushed to obtain leftover fragments, the leftover fragments are mixed evenly with trimethylamine hydrochloride solution and benzyl alkyl dimethyl ammonium salt, stirred and reacted at 55° C. for 4 hours, and then dried to obtain recycled TPU particles;

[0065] Next, the recovered TPU particles were melt-blended with benzoyl peroxide, TPU particles, modified mica powder, and antioxidant 3114 at 150° C. and pelletized underwater to obtain composite TPU particles.

[0066] Finally, the composite TPU particles are placed in a high-pressure reactor, supercritical CO2 is introduced, and the TPU foam material is obtained after full impregnation, pressure release, and water vapor molding at a temperature of 140°C and 20MPa.

[0067] Example 4

[0068] A moisture-curing reactive polyurethane hot melt adhesive for shoes, which differs from Example 1 in that an equal amount of the modified mica powder prepared in Preparation Example 4 is used as the modified mica powder, that is, 3-mercaptopropyltrimethoxysilane is used instead of 3-ureapropyltrimethoxysilane.

[0069] Comparative Example

[0070] Comparative Example 1

[0071] A TPU foam material recycled from leftover shoe materials, which differs from Example 1 in that an equal amount of mica powder is used to replace the modified mica powder.

[0072] Comparative Example 2

[0073] A TPU foam material recycled from leftover shoe materials, which differs from Example 1 in that the modified mica powder is replaced by an equal amount of urea-based silane-modified mica powder.

[0074] Comparative Example 3

[0075] A TPU foam material recycled from leftover shoe materials, which differs from Example 1 in that the modified mica powder is replaced by an equal amount of mica powder modified with di(triethanolamine) diisopropyl titanate.

[0076] Comparative Example 4

[0077] A TPU foam material recycled from leftover shoe materials, which differs from Example 1 in that modified mica powder is not added.

[0078] Performance testing

[0079] 1. Wear resistance test: The friction and wear test was conducted using a MM-200 friction and wear tester. The sample size was 6mm×7mm×30mm. Before each test, the friction surface and the mating part of the sample were polished smooth with 1200# water-abrasive sandpaper, with a roughness of about Ra=0.4μm, and cleaned with acetone. The friction mating part was 45# steel, the mating wheel radius was 20mm, the hardness was HRC42-45, the load was 98N, the linear speed was 0.42m / s, and the dry friction was 2h. Table 1 shows the test results.

[0080] Determination of friction coefficient: During the friction and wear test, the friction torque of the material wear can be directly read from the MM-200 friction and wear tester. The friction coefficient is calculated from the friction torque using formula (1). The average value of three repeated experiments is taken as the final result.

[0081] μ=T / (RP) (1)

[0082] Where T is the friction torque, R is the diameter of the steel wheel (40mm), and P is the load.

[0083] Determination of wear mass loss: Before and after the wear test, the mass of the foaming material was weighed with an electronic balance with a sensitivity of 0.1 mg, the wear mass loss was calculated, and the average value of 3 repeated tests was taken as the final result.

[0084] 2. Vertical rebound test: GB / T 6670-2008 "Determination of rebound properties of soft foam polymeric materials by falling ball method" was used to test the rebound rates of Examples 1-4 and Comparative Examples 1-4;

[0085] 3. Tensile strength measurement: The tensile strength of the foamed materials (specimen thickness: 10-15 mm) prepared in Examples 1-4 and Comparative Examples 1-4 was measured according to the method described in GB / T 6344-2008, and the results are recorded in Table 1, wherein the tensile rate was 500±50 mm / min and the tensile stress was 0.1 KPa.

[0086] Table 1

[0087]

[0088]

[0089] According to the comparison between Example 1 and Example 4 and the data in Table 1, it can be seen that compared with mercaptosilane, ureasilane has a more stable reaction activity. Since the two amino groups in the molecular structure of 3-ureapropyltrimethoxysilane are adjacent to the carbon group, there is a strong conjugation effect, the affinity is reduced, and it has better stability in the polyurethane resin. The prepared foaming material has good wear resistance.

[0090] According to the comparison between Example 1 and Comparative Example 1 and the data in Table 1, it can be seen that when mica powder is added directly to the raw material without modification, the powder cannot be evenly dispersed in the molten system due to poor compatibility with the polyurethane resin, and therefore, the wear resistance of the foaming material is not significantly improved. However, by composite modification of mica powder with urea silane and di(triethanolamine)titanate diisopropyl, the dispersion performance of mica powder in the molten system can be effectively improved, thereby improving the wear resistance of the foaming material while maintaining good resilience and flexibility of the material.

[0091] According to the comparison between Example 1 and Comparative Examples 2-3 and the data in Table 1, it can be seen that the modification effect of mica powder using a single coupling agent is not ideal. On the contrary, urea silane and di(triethanolamine)titanic acid diisopropyl are compounded to obtain a composite modified liquid, and mica powder is modified by the composite modified liquid, so that an excellent interface bonding can be formed between mica powder and polyurethane resin, and urea silane and di(triethanolamine)titanic acid diisopropyl can also produce a synergistic effect, so that the dispersibility and compatibility of the modified mica powder in the molten system are optimal. In addition, since the mica powder particles can effectively absorb the energy generated during the friction process, slow down the destruction of the foaming material, and produce a toughening effect, while improving the wear resistance of the foaming material, it also has good resilience.

[0092] According to the comparison between Example 1 and Comparative Example 4 and the data in Table 1, it can be seen that when the modified mica powder is not added, the wear resistance of the foaming material is poor. On the contrary, after the modified mica powder is added, the powder particles that are debonded when the surface of the foaming material is worn have strong surface activity and are easy to combine with the dual surface to form a fine thin layer, thereby forming a boundary lubrication film on the friction surface, reducing the possibility of direct wear of the material, thereby improving the overall wear resistance of the foaming material.

[0093] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A TPU foam material recycled from shoe material scraps, characterized in that: The invention is prepared from the following raw materials by weight: 45-55 parts of leftover shoe materials, 15-19 parts of recycling agent, 80-90 parts of TPU particles, 8-12 parts of modified mica powder, 1-2 parts of cross-linking agent, 0.6-0.8 parts of antibacterial agent, 0.3-0.5 parts of antioxidant; The raw materials for preparing the modified mica powder include urea silane, di(triethanolamine)titanate diisopropyl and mica powder, and the weight ratio of the urea silane, di(triethanolamine)titanate diisopropyl and mica powder is (0.4-0.6):(0.1-0.3):

10.

2. The TPU foam material recycled from shoe material scraps according to claim 1, characterized in that: The urea silane is one or both of 3-ureapropyltrimethoxysilane and 3-ureapropyltriethoxysilane.

3. The TPU foam material recycled from shoe material scraps according to claim 1, characterized in that: The preparation method of the modified mica powder is: First, mica powder is added to a NaOH solution, stirred at 40-50° C. for 1-2 hours, filtered under reduced pressure to remove excess water and dried to obtain pretreated mica powder; then, urea silane and di(triethanolamine)titanate diisopropyl are mixed to obtain a composite modified liquid, and then the composite modified liquid is added to an ethanol solution, the pH is adjusted to 6.5-7.5, and stirred at a temperature of 50-60° C. for 2-3 hours to obtain a hydrolysis solution; finally, the pretreated mica powder is added to the hydrolysis solution, stirred evenly, filtered and washed after standing for 3-4 hours, and the modified mica powder is obtained after drying.

4. The TPU foam material recycled from shoe material scraps according to claim 1, characterized in that: The recovery treatment agent is trimethylamine hydrochloride solution.

5. The TPU foam material recycled from shoe material scraps according to claim 1, characterized in that: The cross-linking agent is one or more of dicumyl peroxide, di(tert-butylperoxyisopropyl)benzene, benzoyl peroxide, and tert-amyl peroxypivalate.

6. The TPU foam material recycled from shoe material scraps according to claim 1, characterized in that: The antibacterial agent is alkyl trimethyl ammonium salt, dialkyl dimethyl ammonium salt, benzyl alkyl dimethyl ammonium salt.

7. The TPU foam material recycled from shoe material scraps according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 1010, antioxidant 1079, antioxidant 245, antioxidant 1076, antioxidant 3114, and antioxidant 1726.

8. The TPU foam material recycled from shoe material scraps according to claim 1, characterized in that: The TPU particles are polyester polyurethane with a Shore hardness of 50A-45D.

9. A process for preparing a TPU foam material from recycled shoe material scraps as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: S1: crushing the leftover shoe materials to obtain leftover material fragments, mixing the leftover material fragments with a recycling treatment agent and an antibacterial agent, stirring and reacting at 45-55° C. for 3-4 hours, and drying to obtain recycled TPU particles; S2: melt-blending the recycled TPU particles with a cross-linking agent, TPU particles, modified mica powder, and an antioxidant at 140-150° C., and pelletizing underwater to obtain composite TPU particles; S3: placing the composite TPU particles in a high-pressure reactor, introducing a supercritical fluid, fully impregnating at a temperature of 130-140° C. and 16-20 MPa, releasing the pressure, and steam molding to obtain a TPU foam material.

10. The process for preparing TPU foamed material from recycled shoe material scraps according to claim 9, characterized in that: The supercritical fluid in S3 is one or both of supercritical CO2 and supercritical N2.

Citation Information

Cited By

  • A green low-carbon regenerated polymer shoe material particle modification preparation method

    CN122790408A